Mean centering of ratio spectra for colorimetric determination of morphine and codeine in pharmaceuticals and biological samples using melamine modified gold nanoparticles. Issue 37 (30th August 2016) - Mohseni, Naimeh; Bahram, Morteza
Abstract : A simple and sensitive colorimetric sensor was presented for detection of morphine and codeine, based on the aggregation of melamine modified gold nanoparticles. Besides, the practicality of using mean centering of ratio spectra (MCRS) for eliminating the contribution of the reagent blank in nanoparticle-based colorimetric sensing methods is demonstrated. Abstract : Driven by the need to detect narcotics, a new and simple colorimetric assay is presented for the sensitive and visual detection of morphine (MOR) and codeine (COD) using melamine modified gold nanoparticles (MA–AuNPs). Hydrogen-bonding interactions between melamine and the drugs induce aggregation of the AuNPs with a consequent color change from wine red to blue, which can be monitored by a UV-vis spectrophotometer or even the naked eye. Furthermore, we demonstrated the practicality of using mean centering of ratio spectra (MCRS) to remove the contribution of the reagent blank and obtain the net analyte signal in nanoparticle-based colorimetric assays, an aspect which appears to have received no attention to date. This procedure gives more accurate results than the conventional approach using the absorption ratio at maximum wavelength of the aggregated state to the dispersion state ( A agg / A dis ). Comparison of the proposed method with the usual method reveals that MCRS slightly improves the figures of merit of the colorimetric assays. The systems exhibited a linear range from 0.07 to 3 μM for MOR and from 0.03 to 0.8 μM for COD using MCRS. Detection limits (3 σ / m ) of 17 and 9 nM were achieved for MOR and COD, respectively, which are much lower than the therapeutic plasma/serum concentrations and cutoff levels for opiates in urine samples set by the National Institute on Drug Abuse (NIDA). Furthermore, we demonstrate the application of the approach in biological fluids and pharmaceuticals, which suggests that the present assay could satisfy the requirements of clinical toxicology and forensic cases.